Collecting in Context: a Study of the Milwaukee Public Museum's French Paleolithic Faunal Collection - (:unkn) unknown (My University, 2015)
This thesis investigates the history of collecting practices of individual collectors and museums of French Paleolithic archaeological material between 1869 and 1945. During this time period, thousands of French archaeological artifacts were dispersed to museums throughout North America, many with scant provenience. National agendas and the social and economic factors of the time greatly affected their dispersal. The individual agendas of the collector also played a role. This in turn had impacts on the overall understanding of these collections as well as the contemporary construction of archaeological knowledge relating to the study of early humans. A sizable French Paleolithic faunal collection at the Milwaukee Public Museum (MPM) serves as a primary source to investigate this rich history. The faunal remains consist of 245 animal bones, antler fragments, worked bone tools, and conglomerates of bone fragments embedded in a mineralized soil matrix. These materials originate from 11 different Paleolithic sites and/or regions in southern France. The items are identified to taxa and skeletal element, reviewed for evidence of cultural and natural modification, and photographed, with the intent to make the collection available for future researchers.
Keywords: Archaeology; Collecting; Historiography; Museum Studies; Paleolithic; Zooarchaeology